ANALISIS TERHADAP PERTANGGUNGJAWABAN HUKUM KEWENANGAN DISKRESI OLEH PEMERINTAH YANG BERKAITAN DENGAN TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - ASMAYANDI ASMAYANDI (Universitas Mahasaraswati K. Mataram, 2021)
Philosophically, Discretion has a very important position in terms of government administration by public officials, for this reason its juridical-formal arrangement is contained in Law Number 30 of 2014 concerning Government Administration. The formulation of the problem in this study is focused on two things, first, how is the formulation of the concept of discretion in Law Number 30 of 2014 concerning Government Administration? and second, how is the implementation of discretionary authority legal accountability by the government in relation to the criminal act of corruption? From the research results it can be concluded that, firstly, the formulation of the concept of discretion in Law No. 30 of 2014 concerning Government Administration is regulated in Article 22, which provides limits on discretion in two ways, firstly discretion must be issued by an authorized official, and secondly discretion must have clear objectives. And the second form of legal responsibility for discretionary acts related to corruption is in the form of administrative sanctions as regulated in Article 80 of Law No. 30 of 2014.